Outbreaks of measles in Rajasthan in 2014: a cross sectional epidemiological investigation - Singh, Kamaljit; Garg, Rajesh (International Journal Of Community Medicine And Public Health, 2017)
Background: In India, although the measles vaccine is available across the country up to village level, but still India is struggling with mortality and morbidity associated with Measles and its outbreaks. Investigations in measles outbreak help to know the determinants behind it and thus prevent further outbreaks. The outbreaks of measles in Rajasthan were investigated in 2014 by analyzing various socio-demographic parameters. Objective: To assess the epidemiological profile of measles outbreak in Rajasthan in 2014. Methods: The data of the measles surveillance project of Rajasthan was used for analysis. This is an analytical, cross sectional study where 10 districts of Rajasthan having confirmed measles outbreak in 2014 were included. A total of 353 laboratory plus epidemiologically linked measles cases were considered. Statistical analysis: Percentages, proportions and Chi square test were applied. Results: Out of the 23 suspected measles outbreaks subjected for confirmatory laboratory investigation, majority i.e. 14 (60.8%) were found to be of measles. Out of these 14 outbreaks, 353 cases were of measles (Laboratory confirmed + epidemiologically confirmed). Maximum numbers (around 50%) of cases were from the age group 1-4 years. Only 108 (30.6%) cases were vaccinated for measles vaccine. Girl children contributed to about 60 % of the total measles cases. Almost 2/3rd (66.9%) cases were in Muslim families. Conclusions: There was clustering of measles cases in few of the districts adjacent to each other. Measles vaccination coverage in few pockets was poor in outbreak districts. There is a need to boost up measles vaccination coverage with special attention to high risks areas like urban slums etc.